Acute myeloid leukemia in an 86-year-old man with AML1/ETO treated with Homoharringtonine and Arsenic Trioxide: A case report. Issue 13 (March 2019) - He, Zhipeng; Chen, Meiling; Huang, Yiping; Chen, Lili; Wang, Bixin; Wang, Huixian; Yang, Mengting; Xiao, Xueting; Lu, Yanhong; Chen, Jiaying; Wu, Yong
Abstract: Rationale: Acute myeloid leukemia (AML) is a malignantly clonal and highly heterogeneous disease. Although the treatment of AML has brought promising outcomes for younger patients, prognosis of the elderly remains dismal. Innovative regimens are increasingly necessary to be investigated. Patient concerns: We present an 86-year-old AML patient with fever, cough, and sputum production. Diagnoses: A diagnosis of AML with maturation (AML-M2) and AML1/ETO was made. Interventions: The patient was treated with a regimen of Homoharringtonine coupled with arsenic trioxide. Outcomes: The AML-M2 patient with AML1/ETO achieved incomplete remission, but showed few toxic side effects and improved survival. Besides, we analyzed the dynamic counts of complete blood cells during the treatment. The count of white blood cell had a positive correlation with the percentage of blast cells ( r = 0.65), both of which had a negative correlation with the percentage of segmented neutrophils ( r = –0.63, –0.89). Lessons: Homoharringtonine and arsenic trioxide may induce both the apoptosis and differentiation of leukemic cells in AML-M2 with AML1/ETO.